Response of mango (Mangifera indica) cultivars to agro-chemicals for growth and flowering (Current Horticulture, 2024)
An experiment was conducted during 2015-16 and 2016-17 at Agricultural Research Station, Banswara district of Rajasthan  (Maharana Pratap University of Agriculture & Technology, Udaipur) to study the response of different agro-chemicals for  growth and flowering of mango (Mangifera indica). The plants were planted in a square system of planting with a 10m x 10m  spacing. Agro-chemicals, calcium chloride, potassium nitrate, paclobutrazol and sorbitol were used. The treatment combinations  were applied as control (water spray), calcium chloride (0.3, 0.6 and 0.9%), potassium nitrate (1, 2 and 3%), paclobutrazol (500,  1000 and 1500 ppm) and sorbitol (1.5, 2.0 and 2.5%). Application of different agro-chemicals were applied at different stages and  time. Effect of agro-chemicals was found significant for growth and flowering parameters. Paclobutrazol (1500 ppm) was found  better for shoot length and diameter, tree spread, canopy volume and days of fruit setting from flower initiation and flowering  characters viz. date of flower initiation, per cent fruit setting and retention, days to harvest from fruit setting and first flush after  fruiting.
Keywords: Calcium chloride; Potassium nitrate; Paclobutrazol; Sorbitol and agro-chemicals